Revisiting the calpain hypothesis of learning and memory 40 years later - Baudry, Michel; Bi, Xiaoning (Frontiers in Molecular Neuroscience, 2024)
Baudry published in Science a novel biochemical hypothesis for learning and memory, in which they postulated that the calcium-dependent protease, calpain, played a critical role in regulating synaptic properties and the distribution of glutamate receptors, thereby participating in memory formation in hippocampus. Over the following 40 years, much work has been done to refine this hypothesis and to provide convincing arguments supporting what was viewed at the time as a simplistic view of synaptic biochemistry. We have now demonstrated that the two major calpain isoforms in the brain, calpain-1 and calpain-2, execute opposite functions in both synaptic plasticity/learning and memory and in neuroprotection/neurodegeneration. Thus, calpain-1 activation is required for triggering long-term potentiation (LTP) of synaptic transmission and learning of episodic memory, while calpain-2 activation limits the magnitude of LTP and the extent of learning. On the other hand, calpain-1 is neuroprotective while calpain-2 is neurodegenerative, and its prolonged activation following various types of brain insults leads to neurodegeneration. The signaling pathways responsible for these functions have been identified and involve local protein synthesis, cytoskeletal regulation, and regulation of glutamate receptors. Human families with mutations in calpain-1 have been reported to have impairment in motor and cognitive functions. Selective calpain-2 inhibitors have been synthesized and clinical studies to test their potential use to treat disorders associated with acute neuronal damage, such as traumatic brain injury, are being planned. This review will illustrate the long and difficult journey to validate a bold hypothesis.